2016
DOI: 10.1021/acs.chemmater.6b02880
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron-Transfer Quenching of Luminescent Silicon Nanocrystals as a Way To Estimate the Position of the Conduction and Valence Bands by Marcus Theory

Abstract: Photoluminescence of silicon nanocrystals (SiNCs) in the presence of a series of quinone electron acceptors and ferrocene electron donors is quenched by oxidative and reductive electron transfer dynamic processes, respectively. The rate of these processes is investigated as a function of (a) the thermodynamic driving force of the reaction, by changing the reduction potentials of the acceptor or donor molecules, (b) the dimension of SiNCs (diameter = 3.2 or 5.0 nm), (c) the surface capping layer on SiNCs (dodec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 37 publications
(55 reference statements)
2
33
0
Order By: Relevance
“…Locritani et al demonstrated that bonded pyrene molecules can increase brightness of SiNc emission by almost 300% at 378 nm excitation. [29][30][31][32][33] In addition, Fermi et al indicated that a porphyrin chromophore can be also used as antenna for SiNc. However, a significant decrease in PLQY from 40% (for bare SiNc) to 8% (for the conjugates with the porphyrin) was observed upon excitation at 427 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Locritani et al demonstrated that bonded pyrene molecules can increase brightness of SiNc emission by almost 300% at 378 nm excitation. [29][30][31][32][33] In addition, Fermi et al indicated that a porphyrin chromophore can be also used as antenna for SiNc. However, a significant decrease in PLQY from 40% (for bare SiNc) to 8% (for the conjugates with the porphyrin) was observed upon excitation at 427 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In PET, a complex is formed between an electron donor (D) and an acceptor (A); upon excitation, the donor transfers an electron to the acceptor, forming the charge transfer complex [D + A − ]* . For oxidative quenching (where the luminophore is the electron donor), the overall free energy change (Δ G ) for electron transfer is given by:ΔG=nF[]ENC+/NCE00NCnormal*/NCEA/A + wwhere n is the number of electrons involved in the reaction, F is the Faraday constant, E (NC + /NC) and E (A/A − ) are the reduction potentials of the Si NCs and analyte ions (electron acceptors), E 00 ( NC */ NC ) is the one electron potential corresponding to the optical band gap of the Si NCs, while w accounts for the Coulombic interaction between ion pair after electron transfer. For the results reported above, both E (NC + /NC) and E 00 (NC*/NC) remain constant, so the differences in luminescence quenching observed are due to the reduction potentials of the analyte ions.…”
Section: Resultsmentioning
confidence: 99%
“…These results are strongly encouraging for the application of this class of luminescent QDs in LSCs, even if the relatively low QY reported in the paper (46%) is limiting the overall performance of the device. While higher QY values have been reported, the extremely sensitive surface chemistry and the long PL lifetime are responsible for a strong influence of surface trap states and intermolecular excited state quenching phenomena on the QY. In addition, the indirect band gap is responsible for the low absorption coefficient and the limited CRI tunability.…”
Section: Nanomaterials Application In Lscsmentioning
confidence: 94%
“…While higher QY values have been reported, [107] the extremely sensitive surface chemistry and the long PL lifetime are responsible for a strong influence of surface trap states [108] and intermolecular excited state quenching phenomena [109,110] on the QY. While higher QY values have been reported, [107] the extremely sensitive surface chemistry and the long PL lifetime are responsible for a strong influence of surface trap states [108] and intermolecular excited state quenching phenomena [109,110] on the QY.…”
Section: Indirect Band Gap Semiconductorsmentioning
confidence: 95%